Diamond and Carbon Composites and Nanocomposites 2016
DOI: 10.5772/63886
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube (CNT)-Reinforced Metal Matrix Bulk Composites: Manufacturing and Evaluation

Abstract: Need for better understanding and more accurate estimation of radiative fluxes in urban environments, specifically urban surface albedo and exitance, motivates development of new remote sensing and three-dimensional (3D) radiative transfer (RT) modeling methods. The discrete anisotropic radiative transfer (DART) model, one of the most comprehensive physically based 3D models simulating Earth/atmosphere radiation interactions, was used in combination with satellite data (e.g., Landsat-8 observations) to better … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 102 publications
(363 reference statements)
0
5
0
Order By: Relevance
“…Nanocomposites are a focus in materials science and engineering due to their improved properties compared to microscale-reinforced composites [1,2]. In a metallic matrix, the enhancement of a targeted property depends on several factors, including the type of reinforcement, size, amount, degree of dispersion, and the possible interaction between the matrix and an eventual second phase [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites are a focus in materials science and engineering due to their improved properties compared to microscale-reinforced composites [1,2]. In a metallic matrix, the enhancement of a targeted property depends on several factors, including the type of reinforcement, size, amount, degree of dispersion, and the possible interaction between the matrix and an eventual second phase [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the CNTs' physical properties' effect on the mechanical properties, some other essential factors and interactions must be studied. Previous research identified five main interactions, including CNT concentration and aspect ratio, CNT concentration and hydration age, water-to-cement (w/c) and sand-to-cement (s/c) ratios, ultrasonication energy and amplitude, and ultrasonication energy and the surfactant-to-CNTs mass ratio [8,31].…”
Section: Important Parameters Interactionsmentioning
confidence: 99%
“…To overcome the aforementioned issues, both mechanical and chemical techniques were developed to manufacture nanostructured powders. As for the former, the Mechanical Alloying (MA) stands out because it is a method in which the CNTs and the powdered metal matrix are inserted in a ball mill along with steel spheres, which are rotated in a determined velocity to allow the friction energy that is generated to cold-weld the nanotubes on the surface of the metal matrix 5 . It is a relatively inexpensive process, and preserves the involved materials in the solid-state, avoiding possible phase limitations 6 .…”
Section: Introductionmentioning
confidence: 99%